2010
DOI: 10.1007/s00068-010-0062-5
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls of lateral external fixation for supracondylar humeral fractures in children

Abstract: Lateral external fixation is an alternative method for the treatment of displaced or unstable supracondylar fractures in children, facilitating reduction and improving fracture stability. However, iatrogenic radial nerve injury is a risk, and we therefore strongly recommend inserting the proximal pin under direct vision within 2 cm from the fracture line using a drill sleeve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
(19 reference statements)
0
5
0
1
Order By: Relevance
“…In this method, we avoided inserting a K-wire medially, hence the risk of iatrogenic ulnar nerve palsy could be reduced 19 . However, extra care should be taken during the placement of the proximal Schanz pin due to the close proximity to the radial nerve 13 . In our series, we made a mini incision for placement of the proximal Schanz pin under direct vision to avoid any iatrogenic radial nerve injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this method, we avoided inserting a K-wire medially, hence the risk of iatrogenic ulnar nerve palsy could be reduced 19 . However, extra care should be taken during the placement of the proximal Schanz pin due to the close proximity to the radial nerve 13 . In our series, we made a mini incision for placement of the proximal Schanz pin under direct vision to avoid any iatrogenic radial nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…The second Schanz pin was inserted under direct vision after a stab incision with a size 11 blade. This was to prevent injury to the radial nerve which crosses the lateral supracondylar ridge of the humerus at the diaphyseal-metaphyseal junction before it pierces the lateral intermuscular septum to enter the anterior compartment of the arm 13 . The temporary Schanz pin was then removed ( Figure 1C ).…”
Section: Methodsmentioning
confidence: 99%
“…In lateral external fixation of supracondylar humeral fractures, care should be taken to avoid iatrogenic radial nerve palsy. It is recommended to place the proximal Shanz pin under direct vision with a drill sleeve, 2cm proximal to the fracture line to prevent injury to the radial nerve which crosses the lateral supracondylar ridge of the humerus at the diaphyseal-metaphyseal junction [13,19]. Some surgeons may argue that this new technique poses a higher risk of infection due to the presence of more hardwares.…”
Section: Precautionmentioning
confidence: 99%
“…Some surgeons may argue that this new technique poses a higher risk of infection due to the presence of more hardwares. However, current evidence has shown that it has similar or reduced rate of infection compared to the closed pinning method [13,19].…”
Section: Precautionmentioning
confidence: 99%
“…auch als Open-Wedge-Osteotomie und führen hier die sichtbaren radialseitigen Narben als besonders stö-rend an. Die Stabilisierung erfolgt meist durch einen Fixateur externe und kann auch im Sinne einer Kallusdistraktion durchgeführt werden [15][16][17][18][19].…”
Section: Secondary Reconstruction Of the Elbow Joint In Childhood Absunclassified